Clopidogrel and Proton Pump Inhibitors - Tantry, Udaya S.; Kereiakes, Dean J.; Gurbel, Paul A. (JACC. Cardiovascular interventions, 2011)
Dual antiplatelet therapy with aspirin and clopidogrel is associated with a significant reduction in vascular ischemic events; however, gastrointestinal bleeding events are a major concern in high-risk and older patients. Clinical practice guidelines recommend combination therapy with proton pump inhibitors (PPI) and dual antiplatelet therapy to attenuate gastrointestinal bleeding risk. In addition, high on-treatment platelet reactivity has been associated with recurrent ischemic events. Whether or not the pharmacological interaction between clopidogrel and PPI, which results in diminished antiplatelet effect, adversely influences clinical efficacy is highly controversial and the subject of debate. Based on largely anecdotal post-hoc analyses, the U.S. Federal Drug Administration's and European Medicines Agency's recommendations discourage PPI use (particularly omeprazole) in patients treated with clopidogrel. However, many American College of Cardiology/American Heart Association/Society for Cardiovascular Angiography and Interventions experts do not support change in clinical practice guidelines recommendations without adequately powered, prospective, randomized clinical trial data.